Determinants and outcome of multiple and early recurrent cervical artery dissections. (21st August 2018) - Compter, Annette; Schilling, Sabrina; Vaineau, Cloé Juliette; Goeggel-Simonetti, Barbara; Metso, Tiina M.; Southerland, Andrew; Pezzini, Alessandro; Kloss, Manja; Touzé, Emmanuel; Worrall, Bradford B.; Thijs, Vincent; Bejot, Yannick; et al.
Abstract : Objective: To assess putative risk factors and outcome of multiple and early recurrent cervical artery dissection (CeAD). Methods: We combined data from 2 multicenter cohorts and compared patients with multiple CeAD at initial diagnosis, early recurrent CeAD within 3 to 6 months, and single nonrecurrent CeAD. Putative risk factors, clinical characteristics, functional outcome, and risk of recurrent ischemic events were assessed. Results: Of 1, 958 patients with CeAD (mean ± SD age 44.3 ± 10 years, 43.9% women), 1, 588 (81.1%) had single nonrecurrent CeAD, 340 (17.4%) had multiple CeAD, and 30 (1.5%) presented with single CeAD at admission and had early recurrent CeAD. Patients with multiple or early recurrent CeAD did not significantly differ with respect to putative risk factors, clinical presentation, and outcome. In multivariable analyses, patients with multiple or early recurrent CeAD more often had recent infection (odds ratio [OR] 1.81, 95% confidence interval [CI] 1.29–2.53), vertebral artery dissection (OR 1.82, 95% CI 1.34–2.46), family history of stroke (OR 1.55, 95% CI 1.06–2.25), cervical pain (OR 1.36, 95% CI 1.01–1.84), and subarachnoid hemorrhage (OR 2.85, 95% CI 1.01–8.04) at initial presentation compared to patients with single nonrecurrent CeAD. Patients with multiple or early recurrent CeAD also had a higher incidence of cerebral ischemia (hazard ratio 2.77, 95% CI 1.49–5.14) at 3 to 6 months but no difference in functional outcome compared to patients with single nonrecurrent CeAD. Conclusion: Patients with multiple and early recurrent CeAD share similar risk factors, clinical characteristics, and functional outcome. Compared to patients with single nonrecurrent CeAD, they are more likely to have recurrent cerebral ischemia at 3 to 6 months, possibly reflecting an underlying transient vasculopathy.